Pemberdayaan Keluarga melalui Budidaya Tanaman Buah Pekarangan untuk Meningkatkan Ketahanan Keuangan Rumah Tangga di Desa Sasak Panjang - Hamzah, Zeze Zakaria; Anwar, Syaiful; Mujito, Mujito; Hamdani, Muchammad; Muhlis, Muhlis (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to optimize family empowerment in Sasak Panjang Village through the cultivation of backyard fruit plants to enhance household economic resilience. The program was designed with a participatory approach integrating fruit plant cultivation, healthy yard management, and the strengthening of family financial literacy. The activity stages included an initial survey, community discussions, avocado cultivation training, dissemination of productive yard management, and education on financial recording and utilization of harvest yields. Evaluation results showed increased cultivation skills, awareness of yard management, and families’ ability to manage finances independently. This integrated approach has proven capable of encouraging the utilization of yards as a sustainable source of additional income.